Factors associated with the mental health status of pregnant women in China: A latent class analysis - Pei, Yifei; Chen, Qian; Zhang, Ying; He, Chenlu; Wang, Jingjing; Tang, Jie; Hou, Hao; Zhu, Ziqing; Zhang, Xunbao; Wang, Wei (Frontiers in Public Health, 2023)
Background Prenatal mental health is a neglected public health issue that places pregnant women at a higher risk for mental disorders. The purpose of this study was to investigate the influencing factors of prenatal mental disorders and provide a scientific basis to guide and promote the mental health of pregnant women. Methods The study sample comprised 973 women in their first pregnancy, who were in their second trimester and third trimester, who underwent obstetric outpatient checkups at the Maternal and Child Health Hospital in Huai'an, who were recruited in the survey that was conducted from July to December 2017. The Chinese mental health scale (CMHS) was used to assess the mental health of pregnant women. The present study uses the chi-square test to compare the rates of class with different demographic variables, a latent class analysis to identify psychological symptoms, and multiple logistic regression analysis to examine whether the demographics predicted class membership. Results The chi-square test results showed that participants who reported feeling different in the perinatal period (χ2 = 6.35, P = 0.04), having marital satisfaction (χ2 = 15.8, P < 0.001), with an in-law relationship (χ2 = 29.43, P < 0.001), with a friend relationship (χ2 = 24.81, P < 0.001), with basic diseases (χ2 = 8.04, P = 0.02), and taking birth control pills (χ2 = 8.97, P = 0.01) have different probabilities of being classified. Three latent classes were identified: the high symptoms group (6.89%), the moderate symptoms group (20.56%), and the low symptoms group (72.56%). Pregnant women in the third trimester [odds ratio (OR) = 1.83, 95% confidence interval (CI): 1.04–3.25, P = 0.04], with a poor in-law relationship (OR = 2.82, 95% CI:1.45–5.51, P = 0.002), with a bad friend relationship (OR = 3.17, 95% CI: 1.31–7.71, P = 0.01), and who had basic diseases (OR = 1.70, 95% CI: 1.00–2.90, P = 0.04) tended to be classified under the high symptoms group than under the low symptoms group. Pregnant women with a bad friend relationship (OR = 2.15, 95% CI: 1.08–4.28, P = 0.03) and taking birth control pills (OR = 1.51, 95% CI: 1.08–2.11, P = 0.02) were more likely to be placed under the moderate symptoms group than under the low symptoms group. Conclusions A pregnant woman's mental health status factors include feeling different in the perinatal period, those with marital satisfaction, those with an in-law relationship, those with a friend relationship, those with basic diseases, and those taking birth control pills. To ensure a smooth progress of pregnancy and promote the physical and mental health of pregnant women, psychological screening and psychological intervention measures should be strengthened.